Reduction chemistry of neptunium cyclopentadienide complexes: from structure to understanding. Issue 4 (9th February 2017) - Dutkiewicz, Michał S.; Apostolidis, Christos; Walter, Olaf; Arnold, Polly L.
Abstract : Structural investigation on neptunium cyclopentadienyl organometallic complexes in the formal oxidation states II, III, and IV: similarities and differences between Np and U. Abstract : Neptunium complexes in the formal oxidation states II, III, and IV supported by cyclopentadienyl ligands are explored, and significant differences between Np and U highlighted as a result. A series of neptunium(iii ) cyclopentadienyl (Cp) complexes [Np(Cp)3 ], its bis-acetonitrile adduct [Np(Cp)3 (NCMe)2 ], and its KCp adduct K[Np(Cp)4 ] and [Np(Cp′)3 ] (Cp′ = C5 H4 SiMe3 ) have been made and characterised providing the first single crystal X-ray analyses of Np III Cp complexes. In all NpCp3 derivatives there are three Cp rings in η 5 -coordination around the Np III centre; additionally in [Np(Cp)3 ] and K[Np(Cp)4 ] one Cp ring establishes a μ-η 1 -interaction to one C atom of a neighbouring Np(Cp)3 unit. The solid state structure of K[Np(Cp)4 ] is unique in containing two different types of metal–Cp coordination geometries in the same crystal. Np III (Cp)4 units are found exhibiting four units of η 5 -coordinated Cp rings like in the known complex [Np IV (Cp)4 ], the structure of which is now reported. A detailed comparison of the structures gives evidence for the change of ionic radii of ca. −8 pm associated with change in oxidation state between Np III and Np IV . The rich redox chemistry associated with the syntheses is augmented by the reduction of [Np(Cp′)3 ] by KC8 in the presence of 2.2.2-cryptand to afford a neptunium(ii ) complex that is thermally unstable above −10 °C like the U II and Th II complexes K(2.2.2-cryptand)[Th/U(Cp′)3 ]. Together, these spontaneous and controlled redox reactions of organo-neptunium complexes, along with information from structural characterisation, show the relevance of organometallic Np chemistry to understanding fundamental structure and bonding in the minor actinides.